2020
DOI: 10.1111/trf.16196
|View full text |Cite
|
Sign up to set email alerts
|

Residual red cells in blood components: A multisite study of fully automated enumeration using a hematology analyzer

Abstract: Background Manufacture of platelet concentrates (PCs) and plasma may fail to remove all residual red blood cells (rRBCs). Measuring rRBCs for compliance to guidelines has proven challenging, leading to an absence of a consensus methodology. Sysmex hematology analyzers with the Blood Bank mode (BB mode) analysis option offer the potential for automated rRBC counting. We therefore performed a two‐site appraisal of the system. Study Design and Methods Performance characteristics were determined using platelet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Blanco et al showed that rWBC had a mean limit of quantification of 0.002 × 10 9 WBC/L and a good correlation between observed and expected results in linearity studies 6 . Finally, Cavagnetto et al, showed in similar study, this time focusing on rRBC, that the Blood Bank mode had a good correlation between observed and expected results and that the results were consistent with the FC analysis 11 . In our study, the pool of blood donors and blood products came from a single centre, and the number of samples in the different blood products ranged from nine to 55.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Blanco et al showed that rWBC had a mean limit of quantification of 0.002 × 10 9 WBC/L and a good correlation between observed and expected results in linearity studies 6 . Finally, Cavagnetto et al, showed in similar study, this time focusing on rRBC, that the Blood Bank mode had a good correlation between observed and expected results and that the results were consistent with the FC analysis 11 . In our study, the pool of blood donors and blood products came from a single centre, and the number of samples in the different blood products ranged from nine to 55.…”
Section: Discussionmentioning
confidence: 79%
“…showed in similar study, this time focusing on rRBC, that the Blood Bank mode had a good correlation between observed and expected results and that the results were consistent with the FC analysis. 11 In our study, the pool of blood donors and blood products came from a single centre, and the number of samples in the different blood products ranged from nine to 55. In addition, we did not find any samples with residual cells above the safety limits or the LoQ of microscopic examination, so a direct comparison between these two methods was ultimately not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Intact red cells are known to be generally present at lower levels in apheresis compared to whole blood derived platelets [4,32]. Contaminating red cell levels in buffy-coat derived platelets have been demonstrated to be substantially lower in platelets prepared using automated TACSI method compared to semi-automated [33]. Interestingly, France was the only respondent that routinely used TACSI to produce their whole blood derived platelets (70% of their supply), yet the rate of alloimmunisation for D mismatched platelets observed (1%) appears to be similar to other studies [25].…”
Section: Rhdmentioning
confidence: 99%
“…7,8 In general, WBD platelet products have a higher level of contaminating RBCs in comparison with APC platelet products. 9,10 Immunization to RBC antigens poses a variety of complications especially in patients requiring frequent blood transfusion, including difficulty locating compatible blood products and delayed hemolytic transfusion reactions (DHTR) in future transfusions, caused by an anamnestic response of the immune system. 11 Although most DHTR are reported in the context of RBC transfusions, it may also occur after platelet transfusions.…”
Section: Introductionmentioning
confidence: 99%
“…In low‐income countries, almost all platelet products are WBD (platelet‐rich plasma method), as donor platelet collection by apheresis is not available 7,8 . In general, WBD platelet products have a higher level of contaminating RBCs in comparison with APC platelet products 9,10 . Immunization to RBC antigens poses a variety of complications especially in patients requiring frequent blood transfusion, including difficulty locating compatible blood products and delayed hemolytic transfusion reactions (DHTR) in future transfusions, caused by an anamnestic response of the immune system 11 .…”
Section: Introductionmentioning
confidence: 99%